Development of a technological map of a mathematics lesson on the Federal State Educational Standard - Smykovskaia T. K., Trushnikova K. V. (Pedagogy, Psychology, Society, 2023)
The article systematizes the material on the construction of the technological map of the lesson. An example of a step-by-step development of a math lesson for the 5th grade on the topic "Signs of divisibility by 3 and 9" and the author's version of filling out the technological map of the lesson is presented.
Keywords: технологическая карта урока; современный урок математики; конструирование урока; technological map of the lesson; проект урока; урок по ФГОС; lesson project; lesson on FGOS; lesson construction; modern lesson mathematics